DAMPAK KEBIJAKAN PENGEMBANGAN PARIWISATA DENGAN PENDEKATAN EKOWISATA DI PULAU KARIMUNJAWA JEPARA - Ansye Hehalatu (Master of Public Administration, Universitas Slamet Riyadi, 2015)
Tourism is one of the largest foreign exchange earner sectors in Indonesia.This is shown with more development strategy of tourism promotion anddevelopment policy with the ecotourism approach that are friendly toenvironment. Government and community are the two main elements oftourism development policy. Development of mass tourism in Karimunjawabecome a major prop for the government. In terms of increasing local revenuesfor society, in the economic, social, cultural and educational. As for theenvironment, the development of mass tourism has tended to impactnegatively. Environment should get special attention, so that the level ofenvironmental damage to the ecosystem as a tourist attraction should be lower.The high possibility of damage to the ecosystem then force the goverment totake a new policy for Karimunjawa, such as, the development of mass tourismto ecotourism approach. Tourism is expected to bring the change for the benefitof the community, to give a good effect, in accordance with the existing policiesand objectives. This study is aimed to examine the effects that arise in theprocess of implementation of the tourism development policy in Karimunjawa,along with the monitoring, handling and the responsibility of the government ifwhat is happening have a negative impact. This research uses a qualitativeapproach, the method of taking data using in-depth interviews, the raw datafrom the various government agencies involved in the development of tourismin Karimunjawa, as well as the observation that done by researchers inKarimunjawa. In order to have data that more reliable and trustworthy. Resultsof the analysis showed: 1) there is an increase in local revenues in line with theincreasing number of tourists who visit the Karimunjawa. 2) Changes that haveoccurred such as people’s income and enforced many new jobs. 3) A change inpeople’s behavior ranging from children up to adolescence. The low level ofeducation or unstable personality, causing a person can easily influence byforeign cultures without having to be taught. 4) The principle of thedevelopment of mass tourism causing undeniable concern for communities tosustain tourism’s assets. It’s easy of making money instantly causing people ofreluctanting to try to develop economy creative and small business.Keywords: Impact, Tourism, Ecotourism